The impact of family history on non-medullary thyroid cancer. Issue 10 (October 2016) - Nixon, I.J.; Suárez, C.; Simo, R.; Sanabria, A.; Angelos, P.; Rinaldo, A.; Rodrigo, J.P.; Kowalski, L.P.; Hartl, D.M.; Hinni, M.L.; Shah, J.P.; Ferlito, A.
Abstract: Introduction: Around 10% of patients with non-medullary thyroid cancer (NMTC) will have a positive family history for the disease. Although many will be sporadic, families where 3 first-degree relatives are affected can be considered to represent true familial non-medullary thyroid cancer (FNMTC). The genetic basis, impact on clinical and pathological features, and overall effect on prognosis are poorly understood. Methods: A literature review identified articles which report on genetic, clinical, therapeutic and screening aspects of FNMTC. The results are presented to allow an understanding of the genetic basis and the impact on clinical–pathological features and prognosis in order to inform clinical decision making. Results: The genetic basis of FNMTC is unknown. Despite this, significant progress has been made in identifying potential susceptibility genes. The lack of a test for FNMTC has led to a clinical definition requiring a minimum of 3 first-degree relatives to be diagnosed with NMTC. Although some have shown an association with multi-centric disease, younger age and increased rates of extra-thyroidal extension and nodal metastases, these findings are not supported by all. The impact of FNMTC is unclear with all groups reporting good outcome, and some finding an association with more aggressive disease. The role of screening remains controversial. Conclusion: FNMTC is rare but can be diagnosed clinically. Its impact on prognostic factors and the subsequent role in influencing management is debated. For those patients who present with otherwise low-risk differentiated thyroid cancer, FNMTC should be included in risk assessment when discussing therapeutic options.